(untitled) (Vietnam Journal of Community Medicine, 2026)
Background and Objective: Pancreatic cystic lesions (PCLs) are increasingly detected due to advances in imaging modalities. Differentiating between neoplastic cysts (IPMN, MCN, SCN, SPPN, etc.) and non-neoplastic cysts is crucial for determining whether surgical resection or surveillance is appropriate. Endoscopic ultrasound (EUS), with its high-frequency transducer and close proximity to the pancreas, allows for accurate evaluation of high-risk features such as mural nodules, cyst wall thickening, and main pancreatic duct (MPD) dilation, thereby elucidating the true nature of the lesion. Objective: To describe the EUS characteristics of pancreatic cystic lesions. Materials and Methods: A cross-sectional descriptive study was conducted on 25 patients with pancreatic cystic lesions at the Gastroenterology and Hepatology Center, Bach Mai Hospital (May 2024 – May 2025). All patients underwent CT/MRI, EUS ± FNA, and had histopathological confirmation. Data were analyzed using SPSS to calculate sensitivity (Se), specificity (Sp), and diagnostic concordance of EUS and MRI compared with histopathology. Results: Female patients accounted for 56%, with the 60–79-year-old group being the most common (48%). The most frequent symptoms were abdominal pain (60%) and diabetes (56%). On EUS, heterogeneous hypoechogenicity (44%) was associated with malignancy in 72.7%, and solid/thick-walled cysts carried a 50% malignancy risk. A strong correlation was observed between mural nodules ≥ 5 mm and malignancy (70%, p = 0.002). Thickened cyst walls > 2 mm on EUS were significantly associated with malignancy (p = 0.005). EUS showed higher sensitivity and specificity (72.9% and 85.1%, respectively) than MRI (61.9% and 63.9%) in identifying the true nature of lesions compared with histopathology. MPD dilation ≥ 10 mm was mainly observed in IPMN cases and strongly correlated with high-grade dysplasia or malignancy. Conclusion: EUS provides superior diagnostic performance compared with MRI in detecting high-risk features of pancreatic cystic lesions—particularly mural nodules, thickened walls, and heterogeneous echogenicity. Combining EUS and MRI improves diagnostic accuracy and optimizes treatment strategies for patients with pancreatic cystic lesions.